UPLC-ESI-MS/MS and HPTLC Method for Quantitative Estimation of Cytotoxic Glycosides and Aglycone in Bioactivity Guided Fractions of Solanum nigrum L. - Chester, Karishma; Paliwal, Sarvesh; Khan, Washim; Ahmad, Sayeed (Frontiers in Pharmacology, 2017)
Solanum nigrum L., commonly known as black nightshade, is used traditionally for the treatment of liver diseases and inflammation. Investigating the effect of polarity based fractionation of S. nigrum for its hepatoprotective effect on Hep G2 cells in vitro to provide base of its activity by quantifying in steroidal glycosides responsible for hepatoprotective potential. A new UPLC-ESI-MS/MS method following a high performance thin layer chromatography (HPTLC) has been developed and validated for quantification of steroidal glycosides and aglycone (solasonine, solamargine and solasodine, respectively). The in vitro antioxidant potential, total phenolics and flavonoid content were also determined in different fractions. The newly developed UPLC-ESI-MS/MS and HPTLC methods were linear (r2 ≥ 0.99), precise, accurate and showing recovery more than 97%. The n-butanol enriched fraction of S. nigrum berries was found to be the most potent hepatoprotective fraction against all other fractions as it showed significantly (p<0.01) better in vitro anti-oxidant potential than other fractions. Quantification by both methods revealed that, content of steroidal glycosides and aglycones are more than 20% in n-butanol fraction as compared to other fractions. The screened steroidal glycoside n-butanol enriched fraction underwent cytotoxicity and bio-efficacy studies against D-galactosamine and H2O2 induced toxicity in HepG2 cell line showing significant (p < 0.05) liver protection. However developed method can be used for the quality control analysis with respect to targeted metabolites and it can be explored for the pharmacokinetic and pharmacodynamic analysis in future.